“WINNING FREEDOM AND EXACTING JUSTICE”: A. PHILIP RANDOLPH’S USE OF PROVERBS AND PROVERBIAL LANGUAGE - Summerville , Raymond M. (Proverbium - Yearbook, 2020)
This essay explores Randolph’s biographies, writings, and speeches in order to illustrate some of the proverbs and proverbial language that A. Philip Randolph used throughout the Labor and Civil Rights eras. There is no doubt that proverbs and proverbial sayings had a profound influence on Randolph’s life and rhetoric. He used them frequently and effectively in a number of different ways including: during court proceedings, in his many speeches and writings, and in his Messenger magazine which he published with Chandler Owen from 1917 to 1928. Randolph used proverbs from the Bible, important political figures, and also famous literary figures. He also created some proverbs himself. Examining these different areas illustrates that Randolph was fully aware of the political influence that proverbs often have and he sought to utilize this authority whenever necessary.